(untitled) (Research, Society and Development, 2022)
Leaky gut, the leaky gut syndrome, is a disease that is characterized by the loosening of the "TJ" (tight joints), responsible for maintaining a balance of intestinal permeability, so when there is this loosening, a hyperpermeability, increasing the passage of free radicals, pro-inflammatory cytokines and other substances into the bloodstream, causing damage to the functioning of other organs and systems. The objective is search for possible therapies and treatments for Leaky gut. This is a narrative review of the literature. The North American database (PUBMED), Scientific Electronic Library Online (SCIELO), Mendeley, Clinical Trials, Science Direct, among other platforms, were consulted. As inclusion/exclusion criteria, articles were included between 2012 and 2022. When we talk about Leaky gut, despite having little information and research in the area, we found relevant articles and data when talking about its treatment; among the possible treatments and therapies for leaky gut syndrome we can mention some drugs such as lubiprostone, methotrexate, and others, as well as therapies based on medicinal plants such as Flos lonicera thunb, therapies based on supplements such as glutamine and arginine, and also probiotics. Studies show that there are medicines, medicinal plants, supplementary and probiotic therapies that are effective in the treatment of leaky gut syndrome, despite being a new syndrome and recent studies, in addition to professionals and specialized treatments in the area are scarce, which shows that more reliable research is needed than currently available.